Exploring engagement and flow experiences in collective music practices of amateurs, students and professional musicians (Per Musi, 2024)
The purpose of this research was to explore the engagement and flow experiences in collective music practices of amateurs, students, and professional musicians. Based on the first phase of a sequential explanatory mixed methods research design, this article presents the results obtained from an online survey with 102 participants from diverse collective music practices. The results obtained were analyzed using both descriptive and inferential statistics. Some statistically significant differences were observed in the interaction between participant groups (amateurs, students, and professionals) and dimensions of engagement (behavioral, cognitive, and emotional), as reported in the results and discussed in relation to the literature. In summary, we were able to explore and discuss some aspects of engagement, motivation, and flow experience based on the participants’ responses regarding their collective music practices.